2012
DOI: 10.1016/j.ienj.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Violence in the emergency department: An ethnographic study (Part I)

Abstract: Violence in the emergency department (ED) is a significant problem and it is increasing. Nevertheless the problem remains inadequately investigated as most studies that have investigated this issue are descriptive in nature. Although these studies have provided important preliminary information, they fail to reveal the complexities of the problem, in particular the cultural aspects of violence which are crucial for the ED. This paper is part I of a 2-part series which will provide an overview of the background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 21 publications
5
39
0
Order By: Relevance
“…It puts in question certain public policy decisions, modes of hospital organization and management, and individual health-care worker's behavior. It corresponds, however, to realities actually observed and referred to in several studies 16,18,24,26) . It also corresponds to published hospital violence prevention guidelines, which stress the need to analyze the risk of violence as close to the ground as possible in order to be able to identify solutions matching the various causal factors identified in work organization 27,28) .…”
Section: Discussionsupporting
confidence: 73%
“…It puts in question certain public policy decisions, modes of hospital organization and management, and individual health-care worker's behavior. It corresponds, however, to realities actually observed and referred to in several studies 16,18,24,26) . It also corresponds to published hospital violence prevention guidelines, which stress the need to analyze the risk of violence as close to the ground as possible in order to be able to identify solutions matching the various causal factors identified in work organization 27,28) .…”
Section: Discussionsupporting
confidence: 73%
“…Among the first, lengthy waiting times and conditions such as crowded space, contribute to violence occurrence. Beyond those, other studies suggested that in addition to relatively simply measurable factors such as work overload and waiting times, nurse-patient relations have a profound influence on hospital violence [ 20 22 ]. Gaps between staff and patient perceptions were discovered regarding the reasons for violent episodes and the manner in which staff coped with aggression aimed at them [ 23 ] Moreover, as revealed in a companion paper violence assumes different forms and occurs with varying frequencies across different departments, suggesting that perceptions of those involved in violent episodes need to studied more closely [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several countries have published general safety and security recommendations for health personnel [ 15 - 22 ]. However, the nature of workplace violence differs between parts of the health sector as well as between cultures and countries [ 23 , 24 ]. In Norway, the Work Environment Act states that employees should be protected as far as possible against violence and threats (§ 4–3) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%